Analisis Efektivitas Pemberdayaan Ekonomi Umat pada Bank Wakaf Mikro di Pondok Pesantren As’ad Kota Jambi - Umi Himmatul Aliyah; Maulana Yusuf; Sri Rahma (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This research examines how the effectiveness of people's economic empowerment at the Micro Waqf Bank at the As'ad Islamic Boarding School in Jambi City, phenomena that often occur at the Micro Waqf Bank such as